2004
DOI: 10.1093/brain/awh129
|View full text |Cite|
|
Sign up to set email alerts
|

Disrupted daily activity/rest cycles in relation to daily cortisol rhythms of home-dwelling patients with early Alzheimer's dementia

Abstract: Disturbed sleep cycles are the principal cause of institutionalization in dementia, and therefore represent a major clinical problem. They may arise from dysfunction within the circadian clock of the hypothalamus that times and consolidates wakefulness, or from neuropathology in output pathways and/or target sites of the clock specifically controlling sleep and wakefulness. To determine the relationship of disturbed activity cycles to other circadian clock-controlled rhythms, cross-sectional and longitudinal a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
215
3
4

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 302 publications
(236 citation statements)
references
References 61 publications
14
215
3
4
Order By: Relevance
“…The circadian measures did not correlate with dementia severity. These results are concordant with those reported by others 3, 62. The lack of significant differences compared to controls for circadian parameters may be due to the inclusion in our study of mild–moderate AD cases.…”
Section: Discussionsupporting
confidence: 94%
See 3 more Smart Citations
“…The circadian measures did not correlate with dementia severity. These results are concordant with those reported by others 3, 62. The lack of significant differences compared to controls for circadian parameters may be due to the inclusion in our study of mild–moderate AD cases.…”
Section: Discussionsupporting
confidence: 94%
“…This could be due to the intrinsic nature of pathology that produces variable severity of circadian derangement in this disease, as already reported in other case series 3. In our series of mild–moderate AD patients, although we failed to detect a significant difference in terms of circadian parameters (IS, IV, and RA) between AD and controls, there was a subgroup of AD patients with pathological circadian values (>2 SD from the mean of controls).…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…The use of noninvasive actigraphy (usually via a wristworn accelerometer) has been beneficial in monitoring rest/ activity cycles in dementia patients since the early 1990s (14,15). Later rest/activity cycles of home-dwelling AD patients were examined over one year, and those with mild dementia displayed rhythms not significantly different from those of control subjects, whereas those with moderate dementia displayed fragmentation of the rhythm and decreased amplitude, although these effects were not correlated with the severity of the dementia (16). Van Someren et al (17) reported that rhythms were most fragmented in institutionalized AD patients and that higher levels of daytime activity predicted more coherent rhythms, whereas lower levels of daytime activity predicted rhythm fragmentation.…”
Section: Functional Studies Of Circadian Disruption In Admentioning
confidence: 99%